THE EFFECT OF PROFITABILITY, LEVERAGE, FIRM SIZE, AND EARNINGS MANAGEMENT ON TAX AVOIDANCE (CASE STUDY ON FINANCIAL SECTOR COMPANIES LISTED ON IDX 2020-2021) - Wulandari, Fanneisa Fresti; Salsabilla, Sylvania; Romadhoni, Devita Nur; Nurdin, Fajar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This research is aimed to analyze the effect between profitability, leverage, firm size, and earnings management on tax avoidance. This research was conducted by using quantitative method with purposive sampling as the data collection method. The sample of this research is the data of 54 companies in financial sector that are registered on the Indonesia Stock Exchange from 2020-2021. The research analysis used double regression analysis by using SPSS 25 application. The results demonstrate that profitability has a significant positive effect on tax avoidance. Leverage, firm size, and earnings management do not have a positive and significant effect on tax avoidance. Simultaneously, variables profitability, leverage, firm size, and earnings management do not have a positive and significant effect on tax avoidance